Diminished viability of human ovarian cancer cells by antigen-specific delivery of carbon monoxide with a family of photoactivatable antibody-photoCORM conjugates. Issue 2 (25th November 2019) - Kawahara, Brian; Gao, Lucy; Cohn, Whitaker; Whitelegge, Julian P.; Sen, Suvajit; Janzen, Carla; Mascharak, Pradip K.
Abstract : Antibodies conjugated to a photoactive transition metal carbonyl complex afford antigen-directed delivery of cytotoxic carbon monoxide to ovarian cancer cells. Abstract : Carbon monoxide (CO)-releasing antibody conjugates were synthesized utilizing a photoactivatable CO-releasing molecule (photoCORM) and mouse monoclonal antibodies linked by a biotin-streptavidin system. Different monoclonal antibodies raised against different surface-expressed antigens that are implicated in ovarian cancer afforded a family of antibody-photoCORM conjugates (Ab-photoCORMs). In an immunosorbent/cell viability assay, Ab-photoCORMs accumulated onto ovarian cancer cells expressing the target antigens, delivering cytotoxic doses of CO in vitro . The results described here provide the first example of an "immunoCORM", a proof-of-the-concept antibody-drug conjugate that delivers a gaseous molecule as a warhead to ovarian cancer.